2012
DOI: 10.1017/s0016774600000469
|View full text |Cite
|
Sign up to set email alerts
|

Turning the tide: experimental creation of tidal channel networks and ebb deltas

Abstract: Tidal channel networks, estuaries and ebb deltas are usually formed over a period longer than observations cover. Much is known about their characteristics and formation from linear stability analyses, numerical modelling and field observations. However, experiments are rare whilst these can provide data-rich descriptions of morphological evolution in fully controlled boundary and initial conditions. Our objective is to ascertain whether tidal basins can be formed in experiments, what the possible scale effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…Based on scaling arguments (Stefanon et al, 2010), we set up numerical simulations in an attempt to understand the evolution of drainage density of tidal networks from a numerical modelling point of view and also examine to which degree numerical model results agree with the scaling laws. Quantitatively, the numerically simulated tidal networks resemble those obtained in the laboratory experiments (Stefanon et al, 2010(Stefanon et al, , 2012Kleinhans et al, 2012) and some natural back-barrier tide-dominated systems (e.g. the Venice Lagoon and the Dutch Wadden Sea).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Based on scaling arguments (Stefanon et al, 2010), we set up numerical simulations in an attempt to understand the evolution of drainage density of tidal networks from a numerical modelling point of view and also examine to which degree numerical model results agree with the scaling laws. Quantitatively, the numerically simulated tidal networks resemble those obtained in the laboratory experiments (Stefanon et al, 2010(Stefanon et al, , 2012Kleinhans et al, 2012) and some natural back-barrier tide-dominated systems (e.g. the Venice Lagoon and the Dutch Wadden Sea).…”
Section: Discussionsupporting
confidence: 58%
“…Rinaldo et al, 1999a;Marani et al, 2003;Novakowski et al, 2004;Vandenbruwaene et al, 2012a, b), have confirmed that tidal networks show distinctive landscapes and geometric characteristics, because of the highly complicated interactions between various processes such as waves, tides, biological activities and sea level rise. By limiting the number of active processes, controlled laboratory experiments provide an important alternative to gain insight (Stefanon et al, 2010(Stefanon et al, , 2012Vlaswinkel and Cantelli, 2011;Kleinhans et al, 2012;Iwasaki et al, 2013). Moreover, the data obtained from these experiments (or after proper scaling analyses) can be utilised to benchmark numerical models (Tambroni et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Postma et al, 2009;Eggenhuisen and McCaffrey, 2012), tidal experiments (e.g. Tambroni et al, 2005;Stefanon et al, 2010;Kleinhans et al, 2012) and planetary experiments with sediment flows, surface runoff and groundwater outflow (e.g. Kraal et al, 2008;de Villiers et al, 2013;Marra et al, 2014).…”
Section: Stream Table Setup For Bar Formationmentioning
confidence: 99%
“…funnel-shaped tidal channels, tidal mouth bars, etc.) Physical experiments can help bridge this knowledge gap, allowing one to capture delta evolution at a spatial and temporal resolution otherwise impractical in the field (Malverti et al, 2008;Paola et al, 2009;Kleinhans et al, 2012Kleinhans et al, , 2014aStefanon et al, 2012;Braat et al, 2018;Lentsch et al, 2018;Leuven et al, 2018). Physical experiments can help bridge this knowledge gap, allowing one to capture delta evolution at a spatial and temporal resolution otherwise impractical in the field (Malverti et al, 2008;Paola et al, 2009;Kleinhans et al, 2012Kleinhans et al, , 2014aStefanon et al, 2012;Braat et al, 2018;Lentsch et al, 2018;Leuven et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…are typically not well preserved (Dalrymple and Choi, 2007). Recent studies demonstrated that physical experiments are capable of reproducing several typical tidal features, such as ebb deltas (Kleinhans et al, 2012), tidal channel networks (Stefanon et al, 2010;Vlaswinkel and Cantelli, 2011) and tidal estuaries (Kleinhans et al, 2014a). Recent studies demonstrated that physical experiments are capable of reproducing several typical tidal features, such as ebb deltas (Kleinhans et al, 2012), tidal channel networks (Stefanon et al, 2010;Vlaswinkel and Cantelli, 2011) and tidal estuaries (Kleinhans et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%